2023
DOI: 10.1371/journal.pone.0286258
|View full text |Cite
|
Sign up to set email alerts
|

The associations between e-liquid characteristics and its pricing: Evidence from online vape shops

Abstract: Given the increase in electronic cigarette use during the past decade, the objectives of this study are to obtain comprehensive product-level information from online vape shops, which are one of the most common outlets for e-cigarette users to purchase vaping products, especially e-liquid products, and to examine the appeal of various e-liquid product attributes to consumers. We used web scraping and estimation of generalized estimating equation (GEE) models to obtain and analyze data from five popular online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Our database includes e-cigarette brands that are predominately sold in web-based stores; in particular, e-liquid brands are typically not well captured in existing data sources (eg, Nielsen Retail Scanner Data) and our database makes a contribution to the literature by providing those brands. For e-cigarette brands sold on the web, we have also observed that web-based vape shops sell a variety of products with different flavors, nicotine levels, and forms, suggesting the appeals of these brands sold in web-based stores [ 18 , 19 , 32 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our database includes e-cigarette brands that are predominately sold in web-based stores; in particular, e-liquid brands are typically not well captured in existing data sources (eg, Nielsen Retail Scanner Data) and our database makes a contribution to the literature by providing those brands. For e-cigarette brands sold on the web, we have also observed that web-based vape shops sell a variety of products with different flavors, nicotine levels, and forms, suggesting the appeals of these brands sold in web-based stores [ 18 , 19 , 32 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about e-cigarette brands and products sold in vape shops and web-based stores. Moreover, the few studies that examine products sold in these alternative channels suggest that products found in vape shops and web-based stores are significantly different from those in brick-and-mortar stores in terms of prices and product characteristics [ 18 , 19 ]. Therefore, a comprehensive database of brands is needed to identify brand differences by retail channels and assess accurately the e-cigarette market concentration and competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent studies have demonstrated that NVP products are priced differently by nicotine features (e.g. concentration and form), flavors and vegetable glycerin/ propylene glycol ratio [50]. Therefore, the less experience that a smoker or vaper has with NVPs, the more challenging for them to compare the costs of NVPs and cigarettes.…”
Section: ]mentioning
confidence: 99%